The effect of productive SafetyNet program on wasting among under-five children in the rural community of South Gondar Zone, Northwest Ethiopia - Melaku Tadege Engidaw; Alemayehu Digssie Gebremariam (BMC, 2020)
Abstract Background Undernutrition is a significant public health problem in a developing country like Ethiopia. Even if the cause of malnutrition is multifactorial, it is mainly related to socioeconomical, political, and health-related problems. All these problems will lead to more severe nutrient deficiencies among households without assets. The Productive SafetyNet program is implemented for beneficiaries in the rural community to prevent household assets depletion. So, this study aimed to assess the effect of a Productive SafetyNet program on wasting among under-five children in the rural community of South Gondar Zone. Methods A community-based cross-sectional study was done among 803 children paired with their mother/caregivers. Particepnts were selected by a simple random sampling technique. The data were collected by using a structured and pre-tested questionnaire. AnthroPlus software was used to analyse anthropometric data. The data entry employed by EpiInfo version 7.0 software for Windows. Then, the data exported to SPSS version 20.0 to carryout further statistical analysis. The anthropometric index (weight for height) was constructed to determine wasting. Both binary and multivariable logistic regression models were used to identify associated factors. Finally, P-Value ≤0.05 was used to declare statistical significance. Results In this study, the response rate was 95.76%. Of the total participants, 195(25.36%) children were from SafetyNet program beneficiaries. The overall prevalence of wasting was 29.9% (95% CI: 26.6, 33.2%). More than One-fourth of the children from SafetyNet beneficiary households were wasted. While considering all other variables constant, Productive SafetyNet Program reduce wasting by 46% (COR = 0.54. 95% CI (0.37, 0.79)). Wasting were significantly associated with marital status (divorced and/or separated: AOR = 3.33, 95% CI (1.71, 6.45)), being on the SafetyNet program (AOR: 0.63, 95% CI (0.40, 0.99)), family size (AOR = 0.13, 95% CI (0.09, 0.21)), father educational status (AOR: 0.25, 95% CI (0.09, 0.66)), age of the child (AOR = 0.51, 95% CI (0.33, 0.77)), and child dietary diversity score (AOR = 2.99, 95% CI (1.67, 5.35)). Conclusion Wasting was a severe public health problem. In this study, the Productive SafetyNet Program reduce wasting significantly. Marital status, SafetyNet program status, family size, father educational status, age of the child, and dietary diversity were factors associated with wasting among children. Early detection of household asset depletion and SafetyNet program implementation is vital with the usual nutritional assessment and counseling.